2008
DOI: 10.1186/1471-2105-9-315
|View full text |Cite
|
Sign up to set email alerts
|

Parallel and serial computing tools for testing single-locus and epistatic SNP effects of quantitative traits in genome-wide association studies

Abstract: Background: Genome-wide association studies (GWAS) using single nucleotide polymorphism (SNP) markers provide opportunities to detect epistatic SNPs associated with quantitative traits and to detect the exact mode of an epistasis effect. Computational difficulty is the main bottleneck for epistasis testing in large scale GWAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 17 publications
(12 reference statements)
0
118
0
Order By: Relevance
“…According to [9], it would require 1.2 years to do the pairwise epistasis testing of 500,000 SNPs using the serial program on a 2.66 GHz single processor without parallel processing. In this paper, we have provided a cloud epistatic computing model (CEO) for large scale epistatic interactions using the MapReduce framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [9], it would require 1.2 years to do the pairwise epistasis testing of 500,000 SNPs using the serial program on a 2.66 GHz single processor without parallel processing. In this paper, we have provided a cloud epistatic computing model (CEO) for large scale epistatic interactions using the MapReduce framework.…”
Section: Resultsmentioning
confidence: 99%
“…This is the approach we adopt in this paper. [9] provided a tool for processing only singlelocus and two-locus SNPs analysis using supercomputer system on selected types of processors and compilers. However, it is not easy for researchers to rewrite their own programs on specialized hardware.…”
Section: Introductionmentioning
confidence: 99%
“…All these tests were investigated between mild pain versus moderate pain and mild pain versus severe pain (GLM procedure). SNP-SNP interactions in relation to sleep in musculoskeletal pain were observed from the genotype data implementing extended Kempthorne model by software epiSNP [13]. Single locus tests correspond to overall marker effect (M), dominant effect (D) and additive effect (A).…”
Section: Statistical Analysis:-mentioning
confidence: 99%
“…Studies of model organisms suggested epistasis or gene-gene interactions to be a common phenomenon [13,14,15,16], and a number of gene-gene interactions have been reported in gene mapping studies in animals, plants, and other model organisms [17,18,19,20]. However, gene-gene interactions have proven difficult to find in humans [21,22], mainly due to low statistical power caused by the small effect size, the low minor genotype frequency of the multiple-SNP combinations, the large combinatorial number of interaction tests required [14,23], and the lack of control of environmental conditions. Hence, in order to improve the power of detection of gene-gene interactions in human GWAS, many approaches have been developed to prioritize candidate genes or SNPs using biological knowledge from established GWAS hits [6,24], protein-protein interactions (PPIs) [25,26], and pathway information [27].…”
Section: Introductionmentioning
confidence: 99%